Time to add a new priority target for child injury prevention? The case for an excess burden associated with sport and exercise injury: population-based study. Issue 7 (2nd July 2014) - Finch, Caroline F; Wong Shee, Anna; Clapperton, Angela
Abstract : Objective: To determine the population-level burden of sports injuries compared with that for road traffic injury for children aged <15 years in Victoria, Australia. Design: Retrospective observational study. Setting: Analysis of routinely collected data relating to non-fatal hospital-treated sports injury and road traffic injury cases for children aged <15 years in Victoria, Australia, over 2004–2010, inclusive. Participants: 75 413 non-fatal hospital-treated sports injury and road traffic injury cases in children aged <15 years. Data included: all Victorian public and private hospital hospitalisations, using the International Statistical Classification of Diseases and Health Related Problems, 10th Revision, Australian Modification (ICD-10-AM) activity codes to identify sports-related cases and ICD-10-AM cause and location codes to identify road traffic injuries; and injury presentations to 38 Victorian public hospital emergency departments, using a combination of activity, cause and location codes. Main outcome measures: Trends in injury frequency and rate were analysed by log-linear Poisson regression and the population-level injury burden was assessed in terms of years lived with disability (YLD), hospital bed-days and direct hospital costs. Results: Over the 7-year period, the annual frequency of non-fatal hospital-treated sports injury increased significantly by 29% (from N=7405 to N=9923; p<0.001) but the frequency of non-fatal hospital-treated road traffic injury decreased by 26% (from N=1841 to N=1334; p<0.001). Sports injury accounted for a larger population health burden than did road traffic injury on all measures: 3-fold the number of YLDs (7324.8 vs 2453.9); 1.9-fold the number of bed-days (26 233 vs 13 886) and 2.6-fold the direct hospital costs (A5.9 millions vs A2.2 millions). Conclusions: The significant 7-year increase in the frequency of hospital-treated sports injury and the substantially higher injury population-health burden (direct hospital costs, bed-day usage and YLD impacts) for sports injury compared with road traffic injury for children aged <15 years indicates an urgent need to prioritise sports injury prevention in this age group.